1955
DOI: 10.1084/jem.102.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Antibody Production

Abstract: It is the purpose of this paper to draw attention to the very active adjuvant properties of tubercle bacillary wax in potentiating the serum antibody responses to ovalb,rnln, administered as a water-in-oil emulsion, subcutaneously into guinea pigs. Also the morphological effects of the injection of this antigenie mixture, with or without added tubercle bacillary wax, are described.The usefulness of the Freund-type adjuvants in which the antigen is incorporated into the watery phase of a water-in-oil emulsion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1959
1959
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Comparing all groups, the highest antibody production levels in the six weeks were observed in the alum group [28]. These data confirmed the gradual antigen releasing of alum and its ability to create local inflammation [22,36]. In the present study, the constantivity of the antibody rising after the challenge was investigated.…”
Section: Examining Adjuvants and Humeral Immune Systemsupporting
confidence: 76%
See 1 more Smart Citation
“…Comparing all groups, the highest antibody production levels in the six weeks were observed in the alum group [28]. These data confirmed the gradual antigen releasing of alum and its ability to create local inflammation [22,36]. In the present study, the constantivity of the antibody rising after the challenge was investigated.…”
Section: Examining Adjuvants and Humeral Immune Systemsupporting
confidence: 76%
“…By day 7 after injection, inflammation with neutrophil, eosinophil and macrophage cells in the injection site was observed. This inflammation could be related to the effect of adjuvant on the antigenpresenting cells [36,40].…”
Section: Adjuvants Effects On Immune Systemmentioning
confidence: 99%
“…Observations showed that the zone of macrophages built up around the alum deposit contained numerous alum particles. Further observations by White et al (1955b) demonstrated a marked increase in the proliferation of macrophages both locally and in regional lymph nodes when the wax fraction of Mycobacterium tuberculosis was injected in a water-in-oil emulsion, and this was associated with plasma cell proliferation in the regional nodes; this material increased antibody titres to antigens incorporated in the mixture. Humphrey (1963) has demonstrated that mycobacteria in oily emulsions cause a rise in y-globulin in guinea-pigs without any increase in any known antibody.…”
Section: Discussionmentioning
confidence: 95%
“…fractions had any adjuvant activity of the type described by White, Coons & Connolly (1955) in Wax D from other mycobacteria.…”
Section: S C U M M I N S and Othersmentioning
confidence: 99%